Upaya Peningkatan Pengetahuan Remaja Tentang Pentingnya Status Gizi Dalam Penyembuhan Luka di Surakarta - Susilowati, Tri; Prajayanti, Eska Dwi; Purwanto, Purwanto (CV. Rayyan Dwi Bharata, 2026)
Injury is one of the leading causes of death worldwide. According to the World Health Organization (WHO), of the 4.4 million injury-related deaths each year, 3.16 million are caused by unintentional injuries and 1.25 million by violence-related injuries. In Indonesia, the National Police recorded 42,080 accident cases, with 6,004 victims under 17 years old (14.3%). Based on the 2018 Basic Health Research (Riskesdas), the proportion of injuries that disrupt daily activities among those aged 5–14 years is 12.1%, and among those aged 15–24 years is 12.2%, with an overall injury prevalence among school-aged children of 13%. A preliminary study involving 15 adolescents at Muhammadiyah/’Aisyiyah schools showed that most participants (9 adolescents) did not know the importance of nutritional status in wound healing. Furthermore, interviews with the Head of PD Nasyi’atul ‘Aisyiyah (PDNA) Surakarta revealed that no educational sessions had ever been conducted regarding the importance of nutritional status and how to measure it. Therefore, health education is needed to improve adolescents’ knowledge about the role of nutritional status in wound healing. Health education is expected to increase adolescents’ awareness of maintaining proper nutrition to promote faster wound recovery and prevent complications.